Administration and Globalization: A psychological perspective - Perea Rivera, Jóse Luis (2007)
The thematic general of the administration and the globalización must like intention to approach it like axes based on the systematized knowledge or the interpretation that in century XX initiated and comes marking is in an enterprising or apocalyptic prospectiva the direction of the development of the organizations and the human beings in century XXI, that is to say, in the dynamics of the organizations: community, continental countries or blocks, and personal dynamics. The importance of the thematic ones is to have turned in center of attention as much the individual level, organizacional like world-wide, and that we try to treat them in a flexible psychological perspective, presenting/displaying them to way of a proposal of exploratory investigation of approach post facto, in which the administration considered like manager of the development of the organizations, explain if it is the cause or effect of the globalización; also, exposing the criteria that to way of proposals have been expressed like propositive alternatives for their facing in a sistémico criterion and global perspective towards the modernity of century XXI of organizacional change and agreement.